1999
DOI: 10.1897/1551-5028(1999)018<1370:fmdimu>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fish Mercury Distribution in Massachusetts, Usa Lakes

Abstract: Abstract-The sediment, water, and three species of fish from 24 of Massachusetts' (relatively) least-impacted water bodies were sampled to determine the patterns of variation in edible tissue mercury concentrations and the relationships of these patterns to characteristics of the water, sediment, and water bodies (lake, wetland, and watershed areas). Sampling was apportioned among three different ecological subregions and among lakes of differing trophic status. We sought to partition the variance to discover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Growth factors and local lake chemistry were much more important in explaining mercury variation. Lake acidity can be inversely related to Hg concentrations in fish of adjacent lakes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors and local lake chemistry were much more important in explaining mercury variation. Lake acidity can be inversely related to Hg concentrations in fish of adjacent lakes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Even background levels of mercury can result in significant mercury bioaccumulation in fishes. A recent study of 24 ‘clean’ Massachusetts' waterbodies found wet mass muscle mercury concentrations of 0·15 mg kg −1 in brown bullheads Ameiurus nebulosus (Lesueur), 0·31 mg kg −1 in yellow perch Perca flavescens (Mitchill) and 0·39 mg kg −1 in largemouth bass Micropterus salmoides (Lacepède) (Rose et al ., 1999). The concentrations of mercury causing shortening of flagella and increased sperm head lengths, widths and areas in this study are therefore comparable to bioaccumulated mercury levels in wild and laboratory‐exposed fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Control fish had between .1 and .012 ppm, levels typical in fish collected from non-polluted environments lacking conditions which promote metal bioavailability, i.e. low pH and warm temperature (Wiener and Spry, 1996;Rose, et al, 1999). In aquatic systems that have natural mercury deposits or conditions favorable to availability, levels similar to those found in T1 would not be uncommon.…”
Section: Environmental Relevancementioning
confidence: 99%